Sistem Keamanan Berlapis pada Ruangan Menggunakan RFID (Radio Frequency Identification) dan Keypad untuk Membuka Pintu Secara Otomatis - Muhammad Chamdun; Adian Fatchur Rochim; Eko Didik Widianto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2014)
This final project aims to design a door security device using RFID technology (Radio Frequency Identification) and the keypad as a method of access into the room. The system will automatically give warning when the code is entered incorrectly or burglars entered by breaking the door. The microcontroller that is used as the central data processing is ATMega 16 microcontroller ATMEL production and security sensors are used PIR (Passive Infra Red) and magnetic switches.The design begins with a schematic device hardware and software design using CodeVisionAVR programming. Implementation phase includes the implementation of the physical tools, programs, and sensors. The testing phase is done by testing the input sensors and exit switches, siren output devices, DC motor, LCD (Liquid Crystal Display), the RFID reader, keypad, and system controller.The results of room layered security system works according to design. PIR sensors can detect human activities and turn the LED lamp indicator on. Magnetic switch sensors will provide input to the microcontroller to enable or disable the DC motor as the room locking system. Admin menu that is accessed from the keypad is to add users, remove users, see registered users and change the password. User menu which is also accessed using the keypad, work as the room access using a username and password.This study resulted in the layered security. Room access is done using RFIDTag and password. The room piercing detection is done by sensor PIR (Passive Infra Red) and magnetic switches. Alarm used as a piercing action warning. This layered room safety device produces a better security system.